Coach leadership in a crisis context: Investigating effective coach behaviors during the COVID-19 pandemic with a process view - Zhao, Chen; Jowett, Sophia (Frontiers in Psychology, 2022)
Introduction Drawing from the crisis leadership conceptualization, this study aims to investigate coaches’ opinion patterns on effective leadership behaviors during the COVID-19 pandemic. The study used a process view to explore how coaches as leaders act in pre, during, and post-crisis phases. Method Thirty-two fulltime professional coaches (28 males and 4 females) from individual and team sports who experienced the entire COVID-19 pandemic from January 2020 to July 2021 in the United Kingdom were invited to express their perceptions of effective leadership behaviors. The study used Q methodology to analyze coaches’ perceptions and experiences. Result The study revealed that the most effective coach leadership behaviors occurred during-crisis phase, which has the most positive ratings (n = 48) compared to the pre-and post-crisis phases (n = 18). The study’s main findings highlighted different phases of the COVID-19 pandemic demand various effective countermeasures from coaches. These practical and successful experiences were summarized as: division of labor, athlete-centered, team-driven, consulting, safe environment, and online coaching. Discussion The findings of this study further highlight (1) the importance of coach leadership in creating a safe environment as it provides a much better platform to prepare for a pre-crisis stage, (2) that coaches should employ more positive than negative behaviors while interacting with team members more frequently especially during the crisis period, reducing athletes’ negative feelings such as anxiety and worry, and (3) that the online training-related activities and interactions during the crisis time can be expanded to noncrisis times, as a crisis event can have positive implications for the future if handled properly.